#### Answer

$f(2x)=6x-1$
$2f(x)=6x-2$

#### Work Step by Step

We are given:
$f(x)=3x-1$
We evaluate:
$f(2x)=3(2x)-1=6x-1$
$2f(x)=2(3x-1)=6x-2$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f(2x)=6x-1$
$2f(x)=6x-2$

We are given:
$f(x)=3x-1$
We evaluate:
$f(2x)=3(2x)-1=6x-1$
$2f(x)=2(3x-1)=6x-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.